2009
DOI: 10.1387/ijdb.082745de
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a reporter-null allele of Ppap2b/Lpp3and its expression during embryogenesis

Abstract: Our knowledge of how bioactive lipids participate during development has been limited principally due to the difficulties of working with lipids. The availability of some of these lipids is regulated by the Lipid phosphate phosphatases (LPPs). The targeted inactivation of Ppap2b, which codes for the isoenzyme Lpp3, has profound developmental defects. Lpp3 deficient embryos die around E9.5 due to extraembryonic vascular defects, making difficult to analyze its participation in later stages of mouse development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…LPA has essential roles in cortical development, therefore reduced LPA production, due to ATX depletion in neuronal progenitors, might be compensated by other genes involved in LPA homeostasis. Several LPA-regulating genes are expressed in the developing cortex, including phosphatases that degrade LPA such as LPP1 and LPP3 (Giraldi-Guimaraes et al, 2004; Escalante-Alcalde et al, 2007, 2009). Notably, we have shown that increased expression of LPP1, 1a or LPP3 did not affect the proliferation or position of neuroblasts in the ventricular zone.…”
Section: Discussionmentioning
confidence: 99%
“…LPA has essential roles in cortical development, therefore reduced LPA production, due to ATX depletion in neuronal progenitors, might be compensated by other genes involved in LPA homeostasis. Several LPA-regulating genes are expressed in the developing cortex, including phosphatases that degrade LPA such as LPP1 and LPP3 (Giraldi-Guimaraes et al, 2004; Escalante-Alcalde et al, 2007, 2009). Notably, we have shown that increased expression of LPP1, 1a or LPP3 did not affect the proliferation or position of neuroblasts in the ventricular zone.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice that over express LPP1 also have defects in fertility because implantation of LPP1-overexpressing or wild-type embryos into pseudopregnant LPP1 mothers yields a decreased litter size. However, plasma LPA concentrations are not signifi cantly among others ( 106 ). This suggests that LPP3 plays a key role in regulating multiple signaling pathways during development.…”
Section: Nonredundant Functions Of the Lppsmentioning
confidence: 94%
“…LPP3 is expressed in thalamus ventricular areas at E12.5 . This dynamic expression pattern of LPP3 in vasculature could refl ect its critical role during vascular development ( 106 ). A mouse model with conditional knockout of LPP3 in endothelial and hematopoietic cells shows similar defects in vasculogenesis and embryo death to those in mice with global knockout of LPP3 ( 107 ).…”
Section: Lpp3 and The Vasculaturementioning
confidence: 95%
See 1 more Smart Citation
“…For gene expression analysis, the Ppap2b tm2Stw allele ( Ppap2b lacZ ), expressing β-galactosidase (β-gal) as a reporter was used (Escalante-Alcalde et al 2009). For neural inactivation of LPP3, homozygous or heterozygous conditional Ppap2b tm3Stw ( Ppap2b flox ) females were crossed with Tg(Nes-cre)1Kln; Ppap2b tm3Stw / + or Ppap2b tm3Stw / tm3Stw males and their progeny were genotyped by PCR from genomic DNA of neural and non-neural tissues as previously described (Escalante-Alcalde et al 2007).…”
Section: Methodsmentioning
confidence: 99%